Modification of Cardiac Progenitor Cell-Derived Exosomes by miR-322 Provides Protection against Myocardial Infarction through Nox2-Dependent Angiogenesis - Seock-Won Youn; Yang Li; Young-Mee Kim; Varadarajan Sudhahar; Kareem Abdelsaid; Ha Won Kim; Yutao Liu; David J.R. Fulton; Muhammad Ashraf; Yaoliang Tang; Tohru Fukai; Masuko Ushio-Fukai (MDPI AG, 2019)
Myocardial infarction (MI) is the primary cause of cardiovascular mortality, and therapeutic strategies to prevent or mitigate the consequences of MI are a high priority. Cardiac progenitor cells (CPCs) have been used to treat cardiac injury post-MI, and despite poor engraftment, they have been shown to inhibit apoptosis and to promote angiogenesis through poorly understood paracrine effects. We previously reported that the direct injection of exosomes derived from CPCs (CPCexo) into mouse hearts provides protection against apoptosis in a model of acute ischemia/reperfusion injury. Moreover, we and others have reported that reactive oxygen species (ROS) derived from NADPH oxidase (NOX) can enhance angiogenesis in endothelial cells (ECs). Here we examined whether bioengineered CPCexo transfected with a pro-angiogenic miR-322 (CPCexo-322) can improve therapeutic efficacy in a mouse model of MI as compared to CPCexo. Systemic administration of CPCexo-322 in mice after ischemic injury provided greater protection post-MI than control CPCexo, in part, through enhanced angiogenesis in the border zones of infarcted hearts. Mechanistically, the treatment of cultured human ECs with CPCexo-322 resulted in a greater angiogenic response, as determined by increased EC migration and capillary tube formation via increased Nox2-derived ROS. Our study reveals that the engineering of CPCexo via microRNA (miR) programing can enhance angiogenesis, and this may be an effective therapeutic strategy for the treatment of ischemic cardiovascular diseases.